1985
DOI: 10.1136/bmj.290.6464.281
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intraepithelial neoplasia in postmenopausal women with negative cervical cytology.

Abstract: Cervical intraepithelial neoplasia in postmenopausal women with negative cervical cytology Four cases of cervical intraepithelial neoplasia were detected among 50 postmenopausal women in whom cytological examination of a cervical smear yielded negative results, indicating the need for cytological surveillance of women into old age. Patients, methods, and resultsCytological and colposcopic examination of the cervix was performed in 50 women presenting to a menopausal clinic with symptoms of the climacteric befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The false negative rates for the initial screening data were comparable to those reported in the literature 2,4,5,7,9,11,12,[15][16][17]19,24,[26][27][28][29][30][31][36][37][38][39][44][45][46]51 for both the conventional smears and monolayers. The study demonstrated that the high false negative rates experienced in cervical cytology are associated primarily with missed atypical cells.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The false negative rates for the initial screening data were comparable to those reported in the literature 2,4,5,7,9,11,12,[15][16][17]19,24,[26][27][28][29][30][31][36][37][38][39][44][45][46]51 for both the conventional smears and monolayers. The study demonstrated that the high false negative rates experienced in cervical cytology are associated primarily with missed atypical cells.…”
Section: Discussionsupporting
confidence: 72%
“…6,10,13,14,25,50 It has been reported, however, that the CC smear has a false negative rate between 6% and 55%. 2,4,5,7,9,11,12,[15][16][17]19,24,[26][27][28][29][30][31][36][37][38][39][44][45][46]51 False positives are also observed, but since abnormal findings are confirmed histologically, the implications are less critical.…”
mentioning
confidence: 99%
“…Pap test false-positive rates are higher in this group because atrophic cellular changes can mimic neoplastic changes. False-negative results may be obtained due to difficulty in sampling the squamocolumnar junction which has often regressed into the endocervix [21]. Zhao et al [22] recently showed that HPV prevalence in women over the age of 70 with a normal Pap test result is higher than in the 40–70 age group.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect conferred by screening may be age dependent, and postmenopausal women may be less well protected by screening than are younger women 10 . This may be due to age‐related biological differences in the natural history of cervical cancer such as a shorter preinvasive phase 11,12 and/or compromised sensitivity of the cervical smear due to physiological changes of the cervix associated with aging 13,14 …”
mentioning
confidence: 99%